DISTRIBUCION DE LOS FORAMINIFEROS PLANCTONICOS DEL PLIOCENO EN LA PLATAFORMA CONTINENTAL DEL SW DE ESPANA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Planktonic Foraminifera assemblages from cores of a borehole are studied. Depth interval is from 380 m to 2300 m. The drill site is located in the continental shelf of "Golfo de Cadiz" (SW Spain). The distribution of planktonic foraminiferal species is in agreement with Blow's zonation (1969) extending in age from the Messinian to the Pleistocene.
Keywords: Pliocene; Foraminifera SW Spain.